ILRI Assistant Director General Shirley Tarawali becomes chair of GASL - Tarawali, Shirley A. (International Livestock Research Institute, 2020)
A two-minute photofilm of images of Shirley Tarawali, assistant director general of the International Livestock Research Institute (ILRI) and chair of the Global Agenda for Sustainable Livestock (GASL).